2020
DOI: 10.1039/d0cp00627k
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Rashba spin splitting induced by an asymmetrical internal electric field in polar III–VI chalcogenides

Abstract: The Rashba spin splitting of polar group III–VI chalcogenides XABY (A, B = Ga, In; X ≠ Y = S, Se, Te) monolayer is investigated based on the density functional theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Among them, the Rashba coefficient of BiSeI monolayer (1.84 eV Å) is the largest, which is much greater than that of the Janus structures WSeTe (0.92 eV Å) 49 and SeInGaTe (0.67 eV Å). 14 However, we must recognize that it is smaller than the bulk material BiTeI (3.8 eV Å). 46 Next, as a representative, we will emphatically discuss the case of the BiSeI monolayer and the related diagrammatic drawings are plotted in Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Among them, the Rashba coefficient of BiSeI monolayer (1.84 eV Å) is the largest, which is much greater than that of the Janus structures WSeTe (0.92 eV Å) 49 and SeInGaTe (0.67 eV Å). 14 However, we must recognize that it is smaller than the bulk material BiTeI (3.8 eV Å). 46 Next, as a representative, we will emphatically discuss the case of the BiSeI monolayer and the related diagrammatic drawings are plotted in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…13 We investigated the Janus III–VI chalcogenides XABY (A, B = Ga, In; X, Y = S, Se, and Te) monolayers in a previous work and found that a remarkable RSS could be induced by mirror symmetry breaking at the conduction band minimum (CBM). 14…”
Section: Introductionmentioning
confidence: 99%
“…For both models of MS 2 -CrSSe systems, The absence of mirror-symmetry in Janus 2D materials results in different polarization effects, which helps to understand the intrinsic electronic and extrinsic photocatalytic behavior of the materials. [70][71][72][73] The plane-averaged electrostatic potential of all MS 2 -CrSSe heterobilayers for both models is calculated and plotted in Fig. 6(a-d).…”
Section: Results and Dissectionmentioning
confidence: 99%
“…Recently, due to the large band gap, good carrier mobility, high stability, and ease of manufacturing, 12 group III–VI monolayers with the chemical formula of MX (M = In, Ga; X = Se, S, Te) have attracted great interest in nanodevices, 13,14 spintronics, 15,16 thermoelectricity, 17,18 optoelectronics, 19,20 photodetectors, 21,22 as well as catalysts. 23,24 Recently, the GaSe monolayer has been experimentally fabricated from the exfoliation of its bulk phase, 25,26 which exhibits excellent infrared-to-ultraviolet tunable optical activity and tunable electronic character.…”
Section: Introductionmentioning
confidence: 99%